The search for recognition as a life: notes on a Brazilian health care services - Rocon, Pablo Cardozo; Barros, Maria Elizabeth Barros de; Rodrigues, Alexsandro (Argumentum, 2021)
This article, based on the theoretical proposals of the philosopher Judith Butler, analyzes the meanings of recognition of genders produced by women users of a SUS outpatient gender transitioning clinic. Qualitative research was conducted through recorded interviews with nine transsexual women who had undergone gender reassignment surgery. We question that the diagnostic manuals present transsexuality as a pathological condition and a single issue, evidencing the recognition of oneself as being distinct from the recognition of others. We conclude that searches for gender transitioning services reflects attempts to produce a recognition of genders, an effort to produce conditions to permit individuals to appear publicly, to be recognized by others as having livable lives, worthy of protection, and in opposition to discrimination.